The Residential Energy Efficiency Program in Lithuania - Sirvydis, Viktoras (World Bank Group, Washington, DC, 2014)
This case study, which describes the residential Lithuanian energy efficiency (EE) program and lessons learned, was prepared in support of the Energy Sector Management Assistance Program (ESMAP)-funded technical assistance activity Scaling Up of Energy Efficiency in Building in the Western Balkans. During the first period (1996-2004), the World Bank- and donor-funded Energy Efficiency Housing Pilot Project was implemented around investments of US$28.6 million. In addition, technical assistance (TA) was included to facilitate energy auditor market development, establish centers to provide legal advice to homeowner associations (HOAs), train bank officials, and develop a housing agency to further promote EE investments in the residential sector. These changes accelerate the modernization process in Lithuania from about 70 apartment buildings a year to 490 buildings a year. Subsidy procedures for low-income persons were also revised: a May 2013 law to provide support to low-income families was amended to require eligible households to implement a renovation project or risk a cut in their state subsidy from 50 percent to 0 percent for heating costs for a period of three years. This has facilitated the renovation decision-making process among low-income apartment owners.